English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I got 2(2x-1)(x-4) is that what you got?

2007-02-10 05:15:08 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

(2x-4)^2= 4x^2 -16x+16
-(2x-4)= -2x+4


so 4x^2-16x+16-2x+4-12
4x^2-18x +8
2( 2x-9x+4)
2(x-4)(2x-1).
you got the right number.
Congratulation

2007-02-10 05:25:10 · answer #1 · answered by Helper 6 · 1 0

I get the same answer.
Let a = 2x-4
then subbing in you get a^2 -a -12
Factoring gives (a-4)(a+3)
subbing back in for a gives (2x-4-4)(2x-4+3)
Simplifying (2x-8)(2x-1)
Taking out GCF: 2(x-4)(2x-1)

2007-02-10 13:43:01 · answer #2 · answered by lizzie 3 · 0 0

You are correct

(2x - 4)² - (2x - 4) - 12 =

(2x - 4)(2x - 4) = 4x² - 8x - 8x + 16 = 4x² - 16x + 16

4x² - 16x + 16 - (2x - 4) - 12 =

4x² - 16x + 16 - 2x -+4 - 12 =

4x² - 16 - 2x + 16 + 4 - 12 =

4x² - 18x + 8 =

2(2x² - 9x + 4) =

2(2x - 1)(x - 4)

- - - - - - - - -s-

2007-02-10 14:13:12 · answer #3 · answered by SAMUEL D 7 · 0 0

haha sry idk...check it on
www. calculator.com
..they have all calulators u can imagene

2007-02-10 13:22:53 · answer #4 · answered by Kee 1 · 0 1

fedest.com, questions and answers